Developing word recognition through sight method and context clues among educable mentally retarded primary level - Manlavi, Godofredito M. 1944- (1973)
The purpose of the study is to present and suggest an approach in the teaching of word recognition and the developing of skills in word-analysis when reading through the combination of the sight method and context clues. The materials supporting this paper are gathered through intensive research and reading. The sight method and context clues will help in developing the skill of the educable mentally retarded in word recognition and provide them with tools in reading for future use.